MONITORING PENATAAN PERMUKIMAN TEPIAN SUNGAI MAHAKAM DI KOTA SAMARINDA: STUDI KASUS DAERAH SEMPADAN SUNGAI KECAMATAN LOA JANAN ILIR, PALARAN DAN SAMARINDA SEBERANG - Sekar Kedhaton, Arum; Krismondo, Andika (Jurnal Riset Inossa : Media Hasil Riset Pemerintahan, Ekonomi dan Sumber Daya Alam, 2023)
The purpose of this research is to monitor the arrangement of settlements in the Mahakam River area in accordance with the Regulation of the Minister of Public Works and Public Housing Number 28 of 2015, in order to provide recommendations for regional development in Samarinda City and sustainable residential areas. The primary data processing in this study was followed by descriptive analysis. Land cover maps obtained from the National Geospatial Information Agency were analyzed using buffering analysis techniques with a width of 100 meters on the left and right sides of the river to determine the river buffer area and identify settlements that violate the regulations. The 100-meter boundary was chosen based on the provisions of the Regulation of the Minister of Public Works and Public Housing Number 28 of 2015, which defines the transitional urban-rural study area. It was found that settlements encroaching upon the river buffer area covered an area of 2 km2 along three sub-districts, namely Loa Janan Ilir, Samarinda Seberang, and Palaran. The management of the Mahakam River buffer zone is closely related to biogeophysics, socio-economic, and institutional aspects. Managing the river buffer zone is critical for environmental sustainability and protecting communities from flood risks. Proper zoning, urban greening, community participation, law enforcement, and the use of technology are essential to maintain the river's ecosystem and the well-being of the community.